Echocardiographic parameters and vertebral heart size (VHS) in lambs during the neonatal period - Ulian, Carla Maria; Lourenco, Maria Lucia G. [UNESP]; Inamassu, Leticia R. [UNESP]; Souza, Priscilla M.; Mamprim, Maria Jaqueline [UNESP]; Alfonso, Angelica [UNESP]; Chiacchio, Simone B. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2018)
Due to cardiac immaturity, newborns have a different morphology and cardiac output when compared with adults. The purpose of this study was to describe the cardiac changes in echocardiographic characteristics and vertebral heart size (VHS) in newborn lambs during the neonatal period. Twenty-eight healthy Ile de France lambs were evaluated from birth to 35 days old. With the assistance of echocardiography, this study evaluated, both in systole and diastole, indexes related to the right and left ventricles, the aorta (Ao), the left atrium (LA), the E point to septal separation (EPSS) and the thickness of the interventricular septum (VSd, VSs). The left atrium-to-aorta ratio (LA:Ao) was analyzed and both the shortening (SF%) and ejection fractions were calculated (EF%). The VHS was obtained by measuring the heart's long and short axes and comparing it to the thoracic vertebrae. Throughout the first 35 days, the results obtained demonstrated an increased LV:RV ratio when compared to adult lambs. The calculated indexes and the LA:Ao ratio did not present statistically significant differences. The VHS values were normally distributed, presenting a mean of 9.67 vertebrae (v) during the entire period. Both radiographic and echocardiographic parameters showed significant differences between the analyzed moments. The VHS values ranged from 8.4v at the minimum end to 11.2v at the maximum. In order to prevent these changes from being misdiagnosed as heart diseases, this study contributed to take note of neonatal physiological anatomy peculiarities and in addition, it describes the parameters for this age in Ile de France lambs.
Keywords: Cardiac silhouette; cardiovascular system; echocardiography; radiographic examination; neonatal; vertebral heart size; sheep